Le ||gieu des eskies des |Taules et des |Merelles par Nicholes de S. Nicolai [...]. (A. D. 1300). k. 1-64 (1892)
Andrew Fountaine M. S. franz. um 1300
Fountaine Manuscript now in possession of And. Fountaine
Keywords: szachy